Pengaruh Audit Teknologi Infomasi Terhadap Kualitas Audit - Farah Ashma Nadiyah; Balqis Maharani; Dien Noviany Rahmatika (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In the ever-growing digital era, auditing has become an increasingly inseparable part of infIn the ever-growing digital era, auditing is becoming an increasingly inseparable part of information technology. The role of technology in auditing has undergone a significant transformation, leading to what we now know as information technology auditing. This phenomenon not only affects how audits are conducted, but also impacts overall audit quality. Aims to determine the effect of information technology on audit quality. Therefore, the author reviewed several previous research journals originating from various sources including Google Scholar, Semantic Scholar, and Garuda Ministry of Education and Culture. Using the SLR method, the author filtered from these sources 50 journals that were appropriate to the topic. The results of this journal research show that there is a contribution between technology and audit quality in increasing audit efficiency, effectiveness and reliability which can influence audit quality.